Tactical Interventions in the Urban Space (Research, Society and Development, 2019)
The following study discusses, as its main purpose, the occupation of the urban area through tactical interventions. In order to do so, it presents a synthesis of part of the urban problematic in what concerns to the user/space relation, later elucidating the role of tactical interventions in this context, analysis provided by bibliographical research. These interventions are temporary and aim to re-signify and give back the vitality to degraded spaces, acting through punctual, short-term, low-cost and local labor actions. Lastly, it has been found that as the occupation of urban areas and the enjoyment of its landscape gets more intense, the more evident the problems related to the lack of basic infrastructure become. In this context, tactical “solutions” come in hand, they do not solve deep urban problems, but supply the immediate needs, empower the community as a group and reinforce the sense of security and vitality of the city.